Teachers' Professional Competence in Developing Islamic Religious Education and Character Education Learning - Novan Fauzi Adzani; Nurfuadi Nurfuadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe and analyze teachers' professional competence in teaching Islamic Religious Education (IRE) at SMK Tujuh Lima 1 Purwokerto, with a particular focus on subject matter mastery, the selection and implementation of instructional methods, the utilization of learning media, and the conduct of learning assessment. The study employed a qualitative approach with a descriptive research design to gain an in-depth understanding of classroom teaching practices. Data were collected through direct classroom observations, interviews with Islamic Religious Education teachers and students, and documentation related to the instructional process. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through source and technique triangulation. The findings indicate that the teachers' professional competence in teaching Islamic Religious Education at SMK Tujuh Lima 1 Purwokerto has been implemented effectively. This is reflected in the teachers' ability to demonstrate comprehensive mastery of the subject matter, present content systematically and contextually, employ a variety of interactive instructional methods, and utilize learning media, including technology-based media, to enhance students' understanding. Furthermore, the teachers were able to conduct creative and educational assessments and manage the classroom effectively. Although several challenges were encountered, including differences in students' levels of understanding and occasionally less conducive classroom conditions, the teachers successfully addressed these challenges through adaptive instructional strategies and educational approaches, thereby ensuring that the learning process remained effective and meaningful.